Effectiveness of Brain Gym in Improving Learning Concentration in Children: A Literature Study - Hanik Khairun Nisa; Bella Riska Ayu (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This literature review examines the effectiveness of Brain Gym as an intervention to improve children's learning concentration. Brain Gym is a series of physical movements developed to enhance brain function. Several studies in the last decade have suggested that Brain Gym activities can positively influence children's attention span and cognitive performance, particularly in educational settings. Through a review of 20 empirical studies published between 2015 and 2024, this study finds consistent evidence of improved focus and academic engagement among children who participated in regular Brain Gym exercises. The findings suggest that Brain Gym can serve as a complementary approach to conventional teaching strategies, especially for elementary-level learners. Implications for educators and future research are discussed.